2020
DOI: 10.1038/s41564-020-0769-y
|View full text |Cite
|
Sign up to set email alerts
|

LY6E impairs coronavirus fusion and confers immune control of viral disease

Abstract: Zoonotic coronaviruses (CoVs) are substantial threats to global health, as exemplified by the emergence of two severe acute respiratory syndrome CoVs (SARS-CoV and SARS-CoV-2) and Middle East respiratory syndrome CoV (MERS-CoV) within two decades 1-3. Host immune responses to CoVs are complex and regulated in part through antiviral interferons. However, interferon-stimulated gene products that inhibit CoVs are not well characterized 4. Here, we show that lymphocyte antigen 6 complex, locus E (LY6E) potently re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
202
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(220 citation statements)
references
References 38 publications
13
202
5
Order By: Relevance
“…IFITMs inhibit SARS‐CoV, 229E, and MERS‐CoV entry, but promote infection by HCoV‐OC43, a coronavirus that causes the common cold (Huang et al , 2011; Bertram et al , 2013; Warren et al , 2014; Wrensch et al , 2014; Zhao et al , 2014; Zhao et al , 2018). IFITMs, as well as other ISGs, including LY6E and Cholesterol 25‐hydrolase (CH25H), impair SARS‐CoV‐2 replication by blocking the fusion of virions (Pfaender et al , 2020; preprint: Zang et al , 2020; Zhao et al , 2020). Most of the experiments regarding these ISGs have been performed with single‐cycle viral pseudotypes.…”
Section: Introductionmentioning
confidence: 99%
“…IFITMs inhibit SARS‐CoV, 229E, and MERS‐CoV entry, but promote infection by HCoV‐OC43, a coronavirus that causes the common cold (Huang et al , 2011; Bertram et al , 2013; Warren et al , 2014; Wrensch et al , 2014; Zhao et al , 2014; Zhao et al , 2018). IFITMs, as well as other ISGs, including LY6E and Cholesterol 25‐hydrolase (CH25H), impair SARS‐CoV‐2 replication by blocking the fusion of virions (Pfaender et al , 2020; preprint: Zang et al , 2020; Zhao et al , 2020). Most of the experiments regarding these ISGs have been performed with single‐cycle viral pseudotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte antigen 6 complex, locus E (LY6E), was found to impair the cellular fusion of multiple CoVs, including SARS-CoV-2, SARS-CoV-1, and MERS-CoV, by interfering with the S protein-mediated membrane fusion. 108 This suggests that IFN-induced transmembrane (IFITM) protein family members, such as LY6E, could potentially restrict the entry of SARS-CoV-2 and their replication, as was previously shown in the case of SARS-CoV-1. 109 However, IFITM proteins have also been implicated in promoting infection by other human CoVs, such as HCoV-OC43.…”
Section: Interferon Signaling In the Early And Late Covid-19 Phasesmentioning
confidence: 68%
“…× u 1j u 2k u 3m u 4n u 5p u 6 i (1) where G( 1 2 3 4 5 6 ) ∈ R N ×2×2×3×3×2 is a core tensor, and u 1j ∈ R 2×2 , u 2 k ∈ R 2×2 , u 3m ∈ R 3×3 , u 4n ∈ R 3×3 , u 5 p ∈ R 2×2 , and u 6 i ∈ R N ×N are singular values vectors, which can be obtained via the higher-order singular value decomposition (HOSVD) algorithm [2]. To select u 6 i , attributed to selected genes, we need to select u 1j attributed to the genotype, u 2 k attributed to the tissue, u 3m attributed to the treatment, u 4n attributed to the biological replicate, and u 5p attributed to the technical replicate, associated with desired properties.…”
Section: G( 1 2 3 4 5 6 )mentioning
confidence: 99%
“…To achieve this goal, it is essential to understand the mechanism by which SARS-CoV-2 successfully invades human cells. Recently, Pfaender et al [1] demonstrated that host lymphocyte antigen 6 (LY6E) complex impairs coronavirus fusion and confers immune control of viral disease. The authors also used a transcriptome approach to evaluate the effect of infection of mouse hepatitis virus (MHV), a natural mouse pathogen that causes hepatitis and encephalomyelitis, which is a well-studied model of coronavirus infection.…”
Section: Introductionmentioning
confidence: 99%